Implementasi Algoritma Boyer-Moore Pada Chatbot Wisata Yogyakarta - salisah, Tuhfatus; Sari, Bunga Permata; Yulianto, Yogi; Hartanto, Anggit Dwi (Technomedia Journal, 2020)
As the development of technology and increasing newcomers to the city of Yogyakarta, so that the need for information about tourism related in Yogyakarta is also higher. Yogyakarta tourism growth is increasing very rapidly every year as many local and foreign tourists visit the city known as the student town. Therefore, the author intends to build a chatbot that serves as a Virtual Assistant for Yogyakarta tourists. This chatbot is able to provide information to travellers through data stored on the system. The implementation and design of the software resulted in a chatbot built using the Boyer-Moore algorithm. The Boyer-Moore algorithm works by comparing patterns ranging from right to left, so this algorithm becomes an efficient search solution. If there is a pattern string mismatch then the pattern will move towards the left, this gesture will give information how many shifts to match the character that corresponds to the initial pattern. The Boyer-Moore algorithm has an edge over time finding patterns in larger file sizes. From the test results verification, validity submission, and prototype testing conducted on the chatbot system can run well according to the planning. Keywords : chatbot, boyer-moore, touris, tour